Do Monetary Variables Affect to Cryptocurrency Price? Lesson From Indonesia - Citra Anggun Kusumastuty; Dwi Wulandari; Bagus Shandy Narmaditya; Mahirah Kamaludin (Universitas Negeri Malang, 2019)
This study examines the influence of monetary variables and cryptocurrency price. The paper applied Vector Autoregression (VAR) to analyze multivariate time series data. The data used in this study is time series data from January 2014 to December 2017.The findings indicate that there is no significant influence between inflation and the cryptocurrencyprices in the first period. However, the results in the second period,decomposition variant had a significant relationship and experienced a fairly rapid increase of 1.59 per centand continued to increase until the tenth period. The interest rate variable on the price of cryptocurrency has the result of the Variant Decomposition in the first period does not have a significant relationship, while in the second period experienced a significant incline from 6.12 per centand continued to rise until the tenth period.Keywords: Cryptocurrency, bitcoin prices, inflation, money supplyJEL Classification: E43; E44, E51